The Influence of Leadership Style and Organizational Culture on Employee Performance: The Mediating Role of Work Discipline at PT PLN (Persero) UPT Palembang - Raymond Ranthe; Isnurhadi; Farla, Wita (Universitas Muhammadiyah Pontianak, 2026)
Employee performance remains a managerial challenge in Indonesia's electricity transmission sector. This study examines the effects of leadership style and organizational culture on employee performance through work discipline at PT PLN (Persero) UPT Palembang. A quantitative cross-sectional survey was conducted involving 159 employees using a census technique, and the data were analyzed with PLS-SEM. The findings indicate that organizational culture and work discipline significantly improve employee performance, whereas leadership style has no significant direct effect. Work discipline partially mediates the relationship between organizational culture and employee performance. These findings emphasize strengthening organizational culture and work discipline to enhance organizational performance.